Respuesta :

Answer:

Step-by-step explanation:

x²-6x+9 = 0

Factor

(x-3)(x-3) = 0

x = 3

Answer:

x = 3

Step-by-step explanation:

We need to find to numbers that sum up to make -6 but their product is +9 :

-3 and -3 will do :

Now we split -6x into -3x and -3x :

x² -3x -3x + 9 = 0  

Factorise the first 2 terms:

x(x-3)

Keeping the terms inside the bracket the same as the 1st one factorise the next 2 terms :

x(x-3)-3(x-3) = 0

Keep 1 bracket and make another bracket out of the terms that are outside the brackets :

(x-3)(x-3) = 0

Using the integer rule :

a × 0 = 0

We know that one of these brackets are equal to zero :

x-3= 0

Add 3 to both sides :

x = 3

The other bracket is the same so our final answer is x = 3

Hope this helped and have a good day

It would be nice of you to give brainliest